PHYTOCHEMICAL AND ANTIBACTERIAL ACTIVITY OF Nauclea latifolia (AFRICAN PEECH) FRUIT AND LEAF CRUDE EXTRACTS AGAINST SOME PATHOGENIC BACTERIA - I. L., MUHAMMAD; R. G., MUHAMMAD; H., MAJIYA; MOHAMMED, J. N.; SANI, A. R; MOHAMMED, A.; KASSIM, J. Z.; KASSIM, J. Z.; BADEGGI U.M.; AHMED, A. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2021)
The phytochemical screening and antibacterial activity of Nauclea latifolia fruit and leaf extracts against some pathogenic bacteria were investigated. The phytochemical screening was conducted using standard qualitative methods. The antibacterial activity was assayed using the agar well diffusion method. The phytochemical screening of Nauclea latifolia leaf extracts revealed flavonoids, resins and saponins, while fruit extracts indicated the presence of alkaloids, anthraquinones, flavonoids and resins. The test isolates included Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, Staphylococcus aureus and Salmonella Typhi. The Nauclea latifolia methanol leaf extracts showed greater inhibitory effect against the test organisms at 10 and 20 mg/mL concentration with zones of inhibition ranging from (15.00-21.00 mm) and (28.00-31.00 mm), while methanol fruit extracts recorded zones of inhibition ranging from (11.00- 18.00 mm) and (21.00- 27.00 mm) at 10 and 20 mg/mL. The results obtained show that the extracts were more active than ciprofloxacin (positive control) with zones of inhibition ranging from (3.00- 6.00 mm) and (8.00-12.00 mm) at 10 and 20 mg/mL. The result has justified their utilization in the treatment of various ailments associated with the test organisms.